Development and validation of Wordwall-based interactive media for football education learning outcomes - Efri Kumala Sari; Umar Umar; Hendri Neldi; Ardo Okilanda (JPPI (Jurnal Penelitian Pendidikan Indonesia), 2025)
This study aimed to develop and evaluate the validity, practicality, and effectiveness of Wordwall-based interactive learning media for improving football learning outcomes among fifth-grade elementary school students at SDN 10 V Koto Kampung Dalam. This study employed a Research and Development (R&D) approach adapted from the Borg and Gall model. The development process included needs analysis, product design, expert validation, product revision, product testing, and effectiveness testing. The participants consisted of 20 fifth-grade students. Data were collected through expert validation sheets, student response questionnaires, and pre-test and post-test assessments. Data were analyzed using descriptive statistics and paired sample t-tests. The developed media obtained a validity score of 90% from the material expert and 83% from the media expert, indicating that the product was feasible for implementation. Students’ responses reached 85%, categorized as very good. The average learning outcome score increased from 66 in the pre-test to 85 in the post-test, representing a 28.79% improvement. Hypothesis testing showed a significant difference between pre-test and post-test scores (tcount = 7.15 > ttable = 1.729). The Wordwall-based interactive learning media was valid, practical, and effective in improving elementary school students’ football learning outcomes.